(untitled) (Revista Rupturas, 2017)
This article presents a systematization of research related to political-electoral behavior in Costa Rica, and Latin America (including some researches from Spain). In addition a focused on treatment and absenses of youth in this topic. Thus, through a qualitative approach and by the methodology known as a systematic review of the literature, 124 scientific articles were selected from journals indexed mainly in Redalyc.org and Kimuk.conare.ac.cr, which were analyzed with Atlas.ti 7 Software. As a result, it was found that academic interest is focused on political participation apart from the other areas. In the conclusions, it was noticed that political credibility and political trust tend to be confused in their treatment. Meanwhile youth approaches are few in political behavior researches.